Analisis Strategi Pengembangan Usaha Pembibitan Ikan Kerapu (Epinephelus) Skala Rumah Tangga Di Kecamatan Idi Timur Kabupaten Aceh Timur - Nurmalawati (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2024)
The problem of this research is what factors influence internal factors and external factors and what strategies are appropriate in developing a household scale grouper breeding business in Idi Timur District, East Aceh Regency. The aim of this research is to identify what factors influence internal and external factors and analyze development strategies in householdscale grouper breeding businesses in Idi Timur District, East Aceh Regency. The method used in the research is a survey method and an analysis tool using SWOT analysis techniques with a qualitative approach, consisting of strengths, weaknesses, opportunities and threats. From the results of the SWOT analysis (Strengths, Weakness, Opportunities, Threats), three SO (Strength Opportunities) strategies were obtained, three WO (Weakness Opportunities) strategies, three ST (Strength Threat) strategies, and three WT (Weakness Threats) strategies. Of the twelve strategies, one strategy is chosen which is more superior or prioritized using the QSPM (Quantitative Strategic Planning Matrix) analysis tool. From the results of the QSPM analysis, it was found that one strategy was prioritized based on the largest total attractiveness value (TAS). The strategy that got the largest total attractiveness value (TAS) was strategy 4 Keeping the cage area clean from pests and diseases of 5.96.